2014
DOI: 10.1089/vim.2013.0095
|View full text |Cite
|
Sign up to set email alerts
|

Early Cytokine Dysregulation and Viral Replication Are Associated with Mortality During Lethal Influenza Infection

Abstract: Infection with influenza A virus (IAV) leads to acute lung injury and possibly fatal complications, especially in immunocompromised, elderly, or chronically infected individuals. Therefore, it is important to study the factors that lead to pathology and mortality in infected hosts. In this report, we analyze immune responses to infection at a sublethal (0.1 LD 50 ) and lethal (1 LD 50 ) dose of the highly pathogenic IAV A/Puerto Rico/8/34 (PR8). Our experiments revealed that infection with a 1 LD 50 dose induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…The dysregulation of pro‐inflammatory cytokine production induced by IAV was further confirmed in vivo by infection of mice with IAV. The results are consistent with many other studies that upon the infection of IAV, mice produced dramatically higher levels of TNF‐α, IFN‐α, and IL‐6 . Thus, we aimed to find out an agent to inhibit the inflammatory responses of macrophages and alleviate the acute lung injury induced by IAV infection.…”
Section: Discussionsupporting
confidence: 89%
“…The dysregulation of pro‐inflammatory cytokine production induced by IAV was further confirmed in vivo by infection of mice with IAV. The results are consistent with many other studies that upon the infection of IAV, mice produced dramatically higher levels of TNF‐α, IFN‐α, and IL‐6 . Thus, we aimed to find out an agent to inhibit the inflammatory responses of macrophages and alleviate the acute lung injury induced by IAV infection.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies have shown that inflammation during influenza and other respiratory viral infections can cause pathogenesis that is independent of viral levels in the lungs (42,43,(46)(47)(48). Our histopathology data are in agreement with studies that demonstrate excessive inflammatory responses occurring as viral loads are decreasing (25,49). We inoculated mice with influenza A virus PR8 2 days after RV inoculation, which is just prior to the decline in neutrophil numbers in the lungs of RV-infected BALB/c mice (29).…”
Section: Discussionsupporting
confidence: 89%
“…In order to study the effects of viral coinfection on influenza disease pathogenesis, we established a mouse model of coinfection using mouse-adapted influenza A virus strain A/Puerto Rico/ 8/1934 (PR8). PR8 infection in BALB/c mice causes dose-dependent disease severity, in which mortality corresponds with early viral replication and cytokine production, followed by massive cellular infiltration in the lungs (25)(26)(27). To determine how PR8-mediated disease is altered by a mild viral infection, we coinfected mice with human rhinovirus strain 1B (RV1B) or a murine coronavirus, mouse hepatitis virus strain 1 (MHV-1).…”
mentioning
confidence: 99%
“…The influenza virus strain A/Puerto Rico/8/34 (H1N1) used in this study is a highly virulent, mouse‐adapted virus, which was prepared as described previously . An A/Puerto Rico/8/34 (H1N1) infection is treatable with NAI …”
Section: Methodsmentioning
confidence: 99%